Hysterotomy through Colpotomy for the Management of Fetal Maceration in PGF2α Non-Responsive HF Crossbred Cow - Sreeranjani, Raju; Selvaraju, Mani; Sankar, Palanisamy; Varudharajan, Venkatraman (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Fetal maceration is an uncommon condition where the fetus dies after ossification and undergoes microbial  digestion or putrefaction in the uterus till only the mass of  bones remains (Dhindsa et al., 2013; Kumar, 2015). Incomplete  abortion after the third month of gestation is the main  reason for a retained fetal bonymass in the uterus of cows  and buffaloes (Sood et al., 2009). Besides, the cow does not  display severe systemic illness, but the cow may become  slightly febrile, anorexic and depressed with vague signs  of intermittent straining, accompanied by a foul, purulent  vaginal discharge containing small bones (Newman and  Anderson, 2005; Haben, 2020). The retained macerated fetus  by administration of luteolytic drug (PGF2α) and fetal bones  were removed along with purulent discharges manually  (Ramesh et al., 2023). The present case reports the surgical  management of PGF2α non-responsive animal affected with  fetal maceration by hysterotomy through colpotomy.
Keywords: Fetal maceration; buffaloes